KEBIJAKAN FORMULASI GRATIFIKASI SEKSUAL TERHADAP PENYELENGGARA NEGARA - Handrawan Handrawan; Deity Yuningsih; Ahmad Firman Tarta (Fakultas Hukum Universitas Lakidende, 2022)
Sexual gratification in Indonesia can be punished because the practice of sexual gratification can be equated with the practice of corruption because it is classified as a latent crime even though it is difficult to prove but as long as the elements of the perpetrator are people who give bribes to officials and their sexual servants as well as during transactions and services. If the sexual relationship has a connection or has something to do with the authority and position given to an official or state administrator, that person can be charged with regulations related to how the facts of the trial are developed. In addition, the phrase element in Article 12B regarding